A companion to John Adams and John Quincy Adams - Waldstreicher, David (Chichester : Wiley-Blackwell, 2013)
"A Companion to John Adams and John Quincy Adams presents a collection of original historiographic essays contributed by leading historians that cover diverse aspects of the lives and politics of John and John Quincy Adams and their spouses, Abigail and Louisa Catherine."--Publisher's website.
Introduction: The Adams paradox / David Waldstreicher. -- Part I: The First Generation. John Adams: The Life and the Biographers / R.B. Bernstein ; John Adams and Enlightenment / Darren Staloff ; The Revolutionary Politics of John Adams, 1760-1775 / Colin Nicolson ; John Adams in the Continental Congress / Karen N. Barzilay ; John Adams's Political Thought / David J. Siemers ; John Adams, Diplomat / Wendy H. Wong ; John Adams and the Elections of 1796 and 1800 / David W. Houpt ; The Presidency of John Adams / Douglas Bradburn ; John Adams and Religion / John Fea ; Abigail Adams and Feminism / Elaine Forman Crane ; Abigail Adams: The Life and the Biographers / Margaret A. Hogan. -- Part II: The Second Generation. John Quincy Adams: The Life, the Diary, and the Biographers / David Waldstreicher ; John Quincy Adams and National Republicanism / Andrew Shankman ; John Quincy Adams, Diplomacy, and American Empire / John M. Belohlavek ; John Quincy Adams and the Elections of 1824 and 1828 / David P. Callahan ; The Presidency of John Quincy Adams / Padraig Riley ; John Quincy Adams, Internal Improvements, and the Nation State / Sean Patrick Adams ; John Quincy Adams: Apostle of Union / David F. Ericson ; John Quincy Adams, Cosmopolitan / Bethel Saler ; John Quincy Adams and the Tangled Politics of Slavery / Matthew Mason ; John Quincy Adams's Higher Learnings: Rhetoric, Science, and Intellectual History / Marlana Portolano ; A Monarch in a Republic: Louisa Catherine Johnson Adams and Court Culture in Early Washington City / Catherine Allgor and Margery M. Heffron. -- Part III: Images and Legacies. Thomas Jefferson and the John Adams Family / Herbert E. Sloan ; The Adamses on Screen / Nancy Isenberg and Andrew Burstein ; An American Dynasty / Edith B. Gelles.
Includes bibliographical references and index.
Print version record.
Keywords: Adams, John, -- 1735-1826.; Adams, John Quincy, -- 1767-1848.; Adams, John, -- 1735-1826.; Adams, John Quincy, -- 1767-1848.; Adams, John, -- 1735-1826; Adams, John Quincy, -- 1767-1848; Presidents -- United States -- Biography; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- United States -- State & Local -- General; Presidents; United States; Electronic books; Biography; Electronic books